Utilizing Smart Classroom-Based Blended Learning in English for Sports: Students’ Perceptions and Experiences - Alimuddin, Andi Haeriati; Jabu, Baso; Basri, Muhammad (Universitas Cokroaminoto Palopo, 2025)
This study explores students' perceptions and experiences of Smart Classroom-Based Blended Learning in English for Sports at STKIP YPUP Makassar. It examines its effectiveness, user experiences, and challenges. Using a descriptive quantitative survey, data were collected from 30 first-semester students through a structured questionnaire and analyzed using descriptive statistics. Findings show that 84.07% of students had positive perceptions, especially regarding engagement and accessibility. However, only 26.7% found it enhanced collaboration, and technological issues were a concern, with only 16.7% reporting platform compatibility and 13.3% finding internet connectivity sufficient. The results align with Alimuddin et al. (2023), who emphasized the need for adequate training to optimize digital learning. This study contributes to technology-enhanced education, highlighting the need for better infrastructure, digital literacy training, and improved instructional strategies.